2011
DOI: 10.4314/jae.v14i1.64065
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Farmers’ Benefits Derived from Olam Organisation’s Sustainable Cocoa Production Extension Activities in Ondo State, Nigeria

Abstract: The study assessed farmers' benefits derived from Olam organization's sustainable cocoa production extension activities in Ondo state. Structured and validated interview schedule was used to collect relevant information from thirty cocoa farmers, using multistage random sampling technique from cocoa producing towns (Aponmu, Irese, Laagba, Bagbe, Oboto, Igbo-Ore, Igodo, Arogbo, Ago paanu and Agogo) used by Olam in the state. Data were analyzed using percentage, mean and correlation statistics. The findings reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 4 publications
1
7
0
Order By: Relevance
“…This result is in line with the findings of Ozor and Nnaji (2010) which found that farmers in southern Nigeria have an average household size of seven persons. In the same vein Adesope et al (2012), Ozor and Nnaji (2010) and Akinnagbe and Ajayi (2010) in their findings reveal that majority of households in rural areas of Nigeria maintain household size of 6-10 persons. The implication of this is that more family labour will be readily available since relatively large household size is an obvious advantage in terms of farm labour supply.…”
Section: Socio-economic Characteristics Of Respondentsmentioning
confidence: 59%
“…This result is in line with the findings of Ozor and Nnaji (2010) which found that farmers in southern Nigeria have an average household size of seven persons. In the same vein Adesope et al (2012), Ozor and Nnaji (2010) and Akinnagbe and Ajayi (2010) in their findings reveal that majority of households in rural areas of Nigeria maintain household size of 6-10 persons. The implication of this is that more family labour will be readily available since relatively large household size is an obvious advantage in terms of farm labour supply.…”
Section: Socio-economic Characteristics Of Respondentsmentioning
confidence: 59%
“…A possible implication of this result is that respondents have lived long enough in the studied area to be able to give reliable responses to the questions asked. In the same vein Adesope et al (2012), Ozor and Nnaji (2010) and Akinnagbe and Ajayi (2010) in their findings reveal that majority of households in rural areas of Nigeria maintain household size of 6-10 persons. The mean number of years spent in school by the respondents was 12 years implying that majority of the respondents attended secondary school.…”
Section: Socio-economic Characteristics Of Respondentsmentioning
confidence: 75%
“…(2011) that farmers in southern Nigeria had average household size of 7 persons. Similarly, Adesope et al (2012), Ozor and Nnaji (2010) and Akinnagbe and Ajayi (2010) in their studies reveal that majority of households in rural areas of Nigeria maintain household size of 6 -10 persons. The implication of this is that more family labour will be readily available for farm work since relatively large household size is an obvious advantage in terms of farm labour supply (Sule et.al., 1988).…”
Section: Socio-economic Characteristicmentioning
confidence: 82%